Building Sustainable Communities Through Engaged Learning: A University-Community Partnership for Sustained Change in a Central Pennsylvania Coal Town - Vanessa A. Massaro; Shaunna Barnhart; Michael Lasky; Kathy Jeremiah (The University of Alabama, 2022)
University-community partnerships have become more collaborative, decentered, and mutually beneficial in step with changing conceptualizations of knowledge production. However, the implementation of partnerships and projects remains challenging. Models for collaboration are needed in the rural context and for smaller liberal arts universities. This article uses the partnership between Bucknell University and the City of Shamokin to argue for the utility of the sustainable communities framework for conceiving and implementing service-learning. The City of Shamokin previously hosted a prosperous and vibrant downtown district, but the closing of anthracite coal mines and factories has left Shamokin in a decades-long state of economic and population decline. Today, Shamokin faces many challenges brought by this decline: a large elder population, high rates of home and business vacancy, legacies of environmental degradation, and high rates of poverty. In 2014, the Pennsylvania Department of Community and Economic Development declared Shamokin an Act 47 Distressed City, rendering the city bankrupt. In this complex landscape, Bucknell University and its Coal Region Field Station are partnering with and across various local entities, including the city, the Anthracite Outdoor Adventure Area, Northumberland County Planning Department, and the newly formed sustainable development group Anthracite Region for Progress. The sustainable communities framework emphasizes four pillars-economic, social, cultural, and environmental-that serve as a guide for facilitating these ongoing collaborations. These partnerships form the basis of collaborative initiatives developed through community-engaged classroom projects and faculty-led research projects that seek to contribute to partners' visions for a sustainable community.